2020
DOI: 10.1111/irv.12784
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated pandemic 2009 H1N1 influenza A virus human vaccines have different efficacy after homologous challenge in the ferret model

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The ferret has played an important role in infectious viral disease modelling for e.g. influenza A viruses and SARS-CoV-2 [27,35,45]. Hepatic lesions are occasionally reported from laboratory ferrets, including hepatic lipidosis, portal hepatitis, localized hepatic necrosis or abscessation, and these changes are considered non-specific for animal modelling [35,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The ferret has played an important role in infectious viral disease modelling for e.g. influenza A viruses and SARS-CoV-2 [27,35,45]. Hepatic lesions are occasionally reported from laboratory ferrets, including hepatic lipidosis, portal hepatitis, localized hepatic necrosis or abscessation, and these changes are considered non-specific for animal modelling [35,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a similar study conducted in ferrets challenged six weeks after the initial vaccination, generated results consistent with our own findings with NG34 + CAF ® 01 vaccine. This study showed that pdm09 H1N1 vaccines reduced (adjuvanted split vaccine) or had no effect (non-adjuvanted whole vaccine) on the viral shedding from the upper respiratory tract, although the adjuvanted split vaccine did prevent viral replication in the lower respiratory tract of ferrets [ 46 , 47 ]. This suggest that local immunity may play a role for viral shedding but less for pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies using the ferret model showed that cellular immune responses, especially cytotoxicity T cells, play an important role in recovery from influenza virus infection [96,97]. Furthermore, several influenza vaccine platforms have been studied using ferret models [81][82][83]86,87,[98][99][100]. A study by Holzer et al described differential protective efficacy of the Signal Minus FLU vaccine candidate in ferrets and pigs [101].…”
Section: Pathogenesis and Transmissionmentioning
confidence: 99%